THE "E TRIANGLE": EMPLOYMENT, EMPLOYEE AND EMPLOYER IN THE EUROPEAN UNION - Niminet, Liviana Andreea (Studies and Scientific Researches. Economics Edition, 2016)
One of the biggest forces of the European Union is its people, people living and working within this Union. This stands not only for the European Union but for every state, as it is well known that people are the ones that can make a state great or poor. For this reason, the matters regarding labor are a continuous concern both for European Union common institutions as well as for every individual state of the European Union. The main interest, on both sides, is to ensure the best for every part involved in labor process because this means, in the end, added value for everyone. The article focuses on the realities as well as on the expectations regarding the labor field highlighting the most preeminent aspects of the so called "E triangle": employment, employee and employer starting with the most needed definition for each and every one of the above going towards even to proposing remedies for the "spots" needing improvement.